MENTAL CHANGES IN CHILDREN WITH AUTISM SYNDROME - Rakhımova Khurshıdakhan Sadıkovna; Djurabayeva Zumradxon Ma’rufjon qızı (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information about the diseases, conditions and symptoms of autism in children with autism. Children with autistic syndrome have congenital malformations.